2020
DOI: 10.37616/2212-5043.1004
|View full text |Cite
|
Sign up to set email alerts
|

An observational comparison of distal radial and traditional radial approaches for coronary angiography

Abstract: Background Several studies have recently reported regarding feasibility and safety of distal transradial access (d-TRA) in the anatomical snuff-box (ASB); however, literature comparing it with the conventional TRA at the wrist (w-TRA) is sparse. This study compares the technical efficiency and safety of ASB and wrist approaches for TRA for coronary angiography (CAG) and evaluates the radial artery (RA) anatomy at these sites. Methods Two hundred consecutive patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…The meta-analysis showed similar catheterization/puncture failure between dTRA and cTRA, with no statistical significance (OR = 1.94, 95CI [0.97, 3.86], P =0.06; I 2 = 78.5%, P < 0.001). We conducted a sensitivity analysis by removing outlier studies, heterogeneity was significantly reduced after excluding the studies by Bhambhani [ 11 ] and Koutouzis [ 17 ], and there was still no statistical difference (OR = 1.06, 95CI [0.69, 1.64], P =0.788; I 2 = 38.2%, P =0.114). The Egger test suggested the existence of publication bias among the studies ( P =0.015), so we used the trim and fill method to recalculate the effect size: the number of studies did not change, and there was still no statistical difference between them (OR = 1.927, 95CI [0.981, 3.785]), suggesting that the result was robust (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The meta-analysis showed similar catheterization/puncture failure between dTRA and cTRA, with no statistical significance (OR = 1.94, 95CI [0.97, 3.86], P =0.06; I 2 = 78.5%, P < 0.001). We conducted a sensitivity analysis by removing outlier studies, heterogeneity was significantly reduced after excluding the studies by Bhambhani [ 11 ] and Koutouzis [ 17 ], and there was still no statistical difference (OR = 1.06, 95CI [0.69, 1.64], P =0.788; I 2 = 38.2%, P =0.114). The Egger test suggested the existence of publication bias among the studies ( P =0.015), so we used the trim and fill method to recalculate the effect size: the number of studies did not change, and there was still no statistical difference between them (OR = 1.927, 95CI [0.981, 3.785]), suggesting that the result was robust (see Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis showed the total procedure time was similar between dTRA and cTRA, with no statistical significance (SMD = 0.23, 95CI [−0.21, 0.68], P =0.308; I 2 = 91.8%, P < 0.001) (see Figure 9 ). We conducted a sensitivity analysis by removing the outlier study, heterogeneity was significantly reduced after excluding the study by Bhambhani [ 11 ], and there was still no statistical difference (SMD = −0.03, 95CI [−0.17, 0.11], P =0.642; I 2 = 13%, P =0.328). The Egger test showed no publication bias among the studies ( P =0.398).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline studies characteristics included multinational single and multicenter studies published between 2017 and 2022 with enrollment periods spanning from 2016 to 2021. Studies included 11 randomized control trials 4,5,17,22–29 and the remainder were nonrandomized control or observational studies 3,30–45 . The follow‐up postcatheterization ranged from 1 day 28,35,36 to 6 months 42…”
Section: Resultsmentioning
confidence: 99%
“…An observational study by Bhambhani et al in 200 patients undergoing CAG showed increased procedural time with dRA approach (13.4 ± 4.2 vs 9.2 ± 3.1 min; p < 0.01) but insignificant difference in fluoroscopic time between the two groups. 20 With increase in experience and after certain learning curve (at least 50 successful puncture), the procedural time could be decreased further specially the time to access the artery in ASB.…”
Section: Clinical Considerationsmentioning
confidence: 99%